The effect of vitamin K2 supplementation on bone turnover biochemical markers in postmenopausal osteoporosis patients: a systematic review and meta-analysis - Zhang, Zechen; Li, Yuyi; Li, Jinkun; Yuan, Yifeng; Liu, Kang; Shi, Xiaolin (Frontiers in Endocrinology, 2025)
BackgroundOsteoporosis is a metabolic bone disease characterized by decreased bone mass and increased fracture risk. Bone turnover markers, such as osteocalcin (OC), undercarboxylated osteocalcin (ucOC), and other biochemical indicators, are important for assessing bone metabolism. Vitamin K2 influences bone metabolism by enhancing osteocalcin γ-carboxylation.MethodsThis study followed PRISMA guidelines and included randomized controlled trials on the effects of vitamin K2 supplementation on bone turnover biomarkers in postmenopausal osteoporosis patients. Key outcomes included changes in OC, ucOC, and other bone metabolism markers.ResultsNine studies with 2,570 participants were included. Vitamin K2 (VK2) increased osteocalcin (OC; MD 1.86, 95% CI 1.17–2.56) and bone-specific alkaline phosphatase (BAP; MD 1.49, 95% CI 0.98–2.00). It reduced undercarboxylated OC (ucOC; WMD −1.54, 95% CI −2.44 to −0.64) and tartrate-resistant acid phosphatase (TRAP; MD −0.83, 95% CI −1.21 to −0.46). C-terminal telopeptide (CTX) showed a small, statistically significant reduction (MD −0.09, 95% CI −0.14 to −0.05) with uncertain clinical relevance. N-telopeptide (NTX) showed no significant change.ConclusionsVitamin K2 supplementation improves key bone turnover biomarkers, particularly OC and ucOC. These findings support its role in bone metabolism, though further long-term studies are needed to confirm clinical benefits, such as increased bone mineral density.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251087067, identifier CRD420251087067.